Effects of game-based virtual reality on health-related quality of life in chronic stroke patients: A randomized, controlled study. (1st August 2015) - Shin, Joon-Ho; Bog Park, Si; Ho Jang, Seong
Abstract: In the present study, we aimed to determine whether game-based virtual reality (VR) rehabilitation, combined with occupational therapy (OT), could improve health-related quality of life, depression, and upper extremity function. We recruited 35 patients with chronic hemiparetic stroke, and these participants were randomized into groups that underwent VR rehabilitation plus conventional OT, or the same amount of conventional OT alone, for 20 sessions over 4 weeks. Compared to baseline, the VR rehabilitation plus OT group exhibited significantly improved role limitation due to emotional problems ( p =0.047). Compared to baseline, both groups also exhibited significantly improved depression ( p =0.017) and upper extremity function ( p =0.001), although the inter-group differences were not significant. However, a significant inter-group difference was observed for role limitation due to physical problems ( p =0.031). Our results indicate that game-based VR rehabilitation has specific effects on health-related quality of life, depression, and upper extremity function among patients with chronic hemiparetic stroke. Highlights: Rehabilitation can improve physical function and quality of life after a stroke. Virtual reality (VR) is an emerging modality for performing rehabilitation. We evaluated the effects of VR and conventional therapy among stroke patients. VR plus therapy improved specific health-related quality of life items. VR plus therapy also improved depression and physical function measures.